Brodie's abscess associated with soft tissue swelling in an athlete in Abidjan (Ivory Coast) - Kone Seydou Gnombena N'golo; Kone Samba; Dogba Eric; Ouihahi Djekoury Yves Christian; Bana Abdoulaye; Agoh Serge (Open Journal of Trauma - Peertechz Publications, 2020)
Introduction: As very few African publications are found in the literature concerning Brodie's abscesses, we report a rare case of the association of a Brodie's abscess with soft tissue swelling in a sportsman in Abidjan (Ivory Coast). Report case: A 30-year-old patient presented knee pain associated with swelling of the distal third of the thigh as a result of a sports trauma. The diagnosis of a Brodie's abscess was made. Surgical treatment combined with antibiotic therapy was performed. The evolution was favourable. Conclusion: Brodie's abscess is a subacute osteomyelitis that can pose a diagnostic problem with bone tumors. Magnetic Resonance Imaging has a place in the diagnosis. Patient management must be multidisciplinary.